Medium-Term Budget Frameworks in Sub-Saharan African Countries - Allen, Richard; Chaponda, Taz.; Fisher, Lesley; Ray, Rohini (Washington, D.C. : International Monetary Fund, 2017)
More than 15 years ago, many countries in sub-Saharan Africa embarked on a program of budgetary reform, an important element of which was a medium-term budget framework (MTBF). This working paper focuses on the performance of these frameworks in six countries-- Kenya, Namibia, South Africa, Tanzania, Uganda, and Zambia. It assesses the effectiveness of MTBFs in achieving improved fiscal discipline, resource allocation, and certainty of funding, as well as wider economic and social criteria such as poverty reduction and more efficient public investment. In most countries, early successes were not sustained, and budgetary outcomes did not improve, partly for technical reasons, such as poor data and inadequate forecasting methodologies, but also because the reforms were largely supply driven. The paper argues that the development of MTBFs typically falls into four distinct phases. To make the transition from one phase to the next, developing countries should focus on building their capability in macrofiscal forecasting and analysis, and in improving the credibility of the annual budget process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet